الشروط والضوابط الشرعية للغذاء الحلال: خبرة إندونيسيا - Amany Lubis (AHKAM : Jurnal Ilmu Syariah, 2017)
Halal food, which is characterized by lawful and good, has been measured by the standards of what can be eaten and cannot be eaten according to Islamic jurisprudence. The are condition and criteria of halalfood. Supervisory Board of the food products of the Council of Indonesian Ulama sends its inspectors to food factories in order to monitor the stages of production lines, and make sure to the safety of the food. In this article,halal food for Muslim will be discussed, including to unify the standards of halal products in Muslim countries, and implementing the Islamic way of undergoing contracts and transactions. DOI: 10.15408/ajis.v17i1.6222